An Exploration Of Mathematics Education Students' Understanding Padang State University Of Babylonian Mathematics - Yulyanti Harisman; Khairul Zaky (Universitas Swadaya Gunung Djati, 2025)
Mathematics, as a science that has existed since ancient times, has a long history that dates back to the Babylonian civilization. However, not all Mathematics Education students have a good understanding of the mathematics of that era. This research aims to find out and explore Mathematics Education students' understanding of Babylonian Mathematics. This research uses a qualitative approach with literature review and case study methods To achieve these objectives, this research uses two methods, namely literature review and case study. The literature review was conducted to study the development of mathematics in Babylon based on various sources. Meanwhile, case studies were conducted by interviewing five Mathematics Education students of class 2024 who had not completed the History of Mathematics course. The results of this study are expected to provide a clear picture of students' knowledge of Babylonian Mathematics, including the number system, historical heritage, and mathematical concepts developed at that time. In addition, this study will also test students' ability to solve problems related to Babylonian Mathematics. The implication and benefit of this research is to measure how far the understanding of prospective mathematics teacher students related to Babylonian mathematics.